Literatuurwetenschap en uitgeverijonderzoek - Absillis, Kevin (Cahier voor Literatuurwetenschap, 2012)
Over the last few decades cultural sociology and book history have stimulated the study of publishers and their role in the production, distribution, reception and consumption of literature. As such these disciplines have constantly reminded us that literary theory does not study 'autonomous artefacts', but texts which are mediated and influenced by various 'institutions'. But what are the implications? The contributions to this issue of Cahier voor Literatuurwetenschap confront the results of recent and ongoing studies about publishing with the disciplinary idiosyncrasies of general and comparative literature. They not only demonstrate the rich diversity which is typical of this branch of literary studies as far as its method, subject matter and theoretical framework is concerned. They also evaluate acquired ideas and, above all, anticipate new challenges.